Bis N '-(2-oxo-1H-indol-3-ylidene)furan2-carbohydrazidato-kappa O-3,N ',O ' manganese(II) N,N-dimethylformide monosolvate monohydrate - Halim, S.N.A.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2010)
In the title compound, [Mn(C13H8N3O3)(2)]center dot C3H7NO center dot H2O, the metal atom is O,N,O'-chelated by two deprotonated Schiff bases and exists in a distorted octahedral geometry. The N-H groups, the carbonyl group of the DMF molecule and the uncoordinated water molecule engage in N-H center dot center dot center dot O and O-H center dot center dot center dot O hydrogen-bonding interactions, generating a hydrogen-bonded ribbon that propagates along [110].